Experimental and simulation analysis of energy absorption capacity of 3D printed structure design (G) - Koh, Jeremy Heng Wei (Nanyang Technological University, 2023)
Cellular structure designs incorporate patterns of interconnected repeating units for the development of load-bearing structures. These structures have a high strength-to-weight ratio and are heavily utilised in many industries such as aerospace, construction and biomedical science. The design of the cellular structure has a significant impact on its energy absorption capabilities. Characteristics such as geometry, size and shape in a cellular structure affect the energy absorption capacity. A unit design can be as simple as a hexagonal shape on a plane that has been elongated on the axis perpendicular to it. Conversely, it could be as complex as a unit cell with geometries within a plane changing throughout the axis perpendicular to it. Manufacturing cellular structure designs using traditional manufacturing methods such as casting and machining poses many challenges. Casting moulds are costly due to the intricacy and precision of their designs. Special tools are required for machining to replicate the intricate designs. New manufacturing methods, such as additive manufacturing, help to address these issues. This method builds a 3-dimensional object layer by layer based on data presented in a digital design file. Complex shapes and geometries can be easily manufactured using this method, allowing a reduction of manufacturing costs. This research aims to understand the energy absorption capabilities of a cellular structure design with complex geometry under various loading conditions. Finite element analysis will be used to simulate the deformation and understand the mechanical properties of the structure under various loading scenarios. Comparison between different mesh sizes available for finite element analysis within the simulation program will be analysed first to choose a suitable mesh size with the appropriate amount of waiting time needed to run the simulation. This is followed up by the study on the effect of different compression speeds for the compression test of the structure and ends with the testing of different impact speeds for the impact testing.